Energy management system for educational buildings using the prime narrowband PLC standard - Dulay, Ann E. (Animo Repository, 2017)
Energy Management System (EMS) plays a big role in the realization of the Smart Grid. In this research, an EMS for a school building is implemented using the narrowband Power Line Communications (NBPLC) technology based on the PRIME standard. This study demonstrates the utilization of the NBPLC for EMS application. Four C2000 PLC modem from Texas Instrument are used as base node (BN) and service nodes (SN). The base node is connected to the host PC while the service nodes are connected to the appliances in the corresponding rooms of the building. The host PC contains the program that sends a command to a particular service node depending on the class schedule in that room. The program is a graphical user interface developed using Matlab. The commands are the basic turning ON and turning OFF of appliances. The program through the base node sends the ON command to the specific service node of the room where a class is scheduled. A motion detection feature is included to anticipate events where the room with a scheduled class may be empty because of alternative classes, called-off classes, or class suspension. The motion sensor is connected to the service node. The BN requests for the motion sensor status thirty minutes after the start of the class period. If no motion is detected, the program sends an OFF command to the corresponding service node. This positively reduces power consumption and consequently reduces energy wastage. To determine the energy wastage without the system in place, kiloWattmeter was installed in three rooms and the energy consumption was recorded for the whole term comprising 14 weeks. The total consumption read from the meter was 2,736.2 kWhrs. An average consumption per hour was computed based on the first reading of the kWhr meter whereby all the appliances in the rooms are turned on. This is the basis in determining the consumption of three rooms considering only the times where the room has a schedule class. The consumption could have just been 2,089.7 kWhrs. This translates to wastage of 646.5 kWhrs. While this value is relative, if the whole campus with more than a hundred rooms is considered, the impact of such wastage is huge. © 2006-2017 Asian Research Publishing Network (ARPN). All rights reserved.